Expression of the P-glycoprotein Homologue1 on food vacuoles isolated from Chloroquine-sensitive and resistant Plasmodium falciparum strains - Lindt, Meinrad (Division of Clinical Pharmacology, 2018)
Worldwide occurrence of chloroquine resistance is an expanding problem in prophylaxis and treatment of malaria. Similarities between the drug resistance phenotype in certain cancers and in malaria suggest that homologue multidrug resistance proteins might be involved in the mechanism of resistance. In this thesis, the expression of a putative multidrug resistance protein of the malaria parasite Plasmodium falciparum, the P-glycoprotein homologue1 (Pgh1), was quantified on food vacuoles, the site of action of chloroquine. Chloroquine susceptibility was determined in 8 different P. falciparum strains. Food vacuoles were isolated from trophozoites of two chloroquine-sensitive (307 and D10) and three chloroquine-resistant (FAC8, K1 and RSA 11) strains. Antibodies against an 18 amino acid long peptide of Pgh1 were raised, as well as two other antibodies against the N-terminal ATP-binding site and the C-terminus of Pgh1. With these antibodies, Pgh1 was detected on isolated food vac.uoles and on trophozoites by immunoblotting. The exact Pgh1 expression levels on food vacuoles were measured with digital image analysis. The chloroquine-sensitive strains 307 and D10 and the chloroquine-resistant strains K1 and RSA 11 expressed equal amounts of Pgh1. The chloroquine-resistant FAC8 strain expressed at least three times more vacuolar Pgh1. No correlation was found between chloroquine IC₅₀ and vacuolar Pgh1 expression levels. Phosphorylation studies on intact food vacuoles indicated that Pgh1 is not a major kinase substrate.